The information generated from bar coding a tool for trend forecasting (a case study on Giordano Philippines) - Bince, Ann Margareth Corsanes
The bar coded inventory system (BIS) has been known for several years to have served several process industries in the management of inventory. In the Philippines only several companies employ this system as part of their inventory management. It is in this regard that the researcher conducted a study on the possible applications of the bar coded inventory system and whether the information generated from BIS can be used as a tool for accurate trend forecasting. The descriptive method of research was utilized and the self-administered questionnaire and interview were the instruments used for collecting data. The respondents for the study were all the members of the Giordano Philippines forecasting team. This study was able to determine that the information generated from BIS is utilized as a tool for trend forecasting in Giordano Philippines. The other applications of the information were: consolidation, distribution, replenishment, etc. The study also showed that the level of usability and clarity of the information increases as the company achieves more successful trend forecasts. Moreover, the study revealed that software called "Retail Pro" is used to maximize and optimize the study of the information generated from BIS.